ANTICIPATING FINANCIAL AND DATA PRIVACY RISK: ASSESSING LEGAL RIGHTS AND RESPONSIBILITIES IN ONLINE SOCIAL GATHERING IN INDONESIA - Yulia Kusuma Wardani; Torkis Lumban Tobing; Putri Ariyanti; Depri Liber Sonata; Dianne Eka Rusmawati (Indonesia Private Law Review, 2023)
The industrial revolution 4.0 has given rise to online social gatherings, which offer an alternative to traditional face-to-face interactions. The agreements and arrangements between organizers and members of social gatherings are conducted through online communication media, resulting in virtual agreements. While these gatherings have numerous benefits, including convenience and accessibility, they expose members to threats such as data privacy violations and financial risks. This study highlights the need to understand and navigate the risks associated with online social gatherings and emphasizes the importance of legal protections for their members. Furthermore, this paper aims to examine the mechanism of online social gatherings, assess their potential risks, and analyze the legal protections available to members in Indonesia. The study employs empirical juridical research methods with a descriptive research type, including collecting sources from reading materials, such as books and laws and regulations, and conducting interviews. The research finds that online social gathering agreements can be classified into innominate agreements, standard agreements, and reciprocal agreements. However, in practical terms, online social gatherings may pose serious threats to members due to privacy violations and fraud-related risks. Indonesia has enacted several provisions and litigation processes to mitigate these potential risks to protect members from such harm. Maintaining a balance between the benefits and risks of online social gatherings is essential to ensure their continued positive impact on society.